(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2024)
Polymictic gravels exploited in the vicinity of Rugvica, SE from Zagreb, comprise clasts of various lithology, colour, shape, and size. Pebbles are composed of sedimentary, volcanic and, sporadically, metamorphic rocks. During the field work we recognized fossils in the abundant carbonate pebbles. Most of the carbonate clasts are rounded, discoidal in shape, varying in colour from white to dark grey, almost black. Pebbles were measured by a calliper and petrographic thin sections were prepared from fossiliferous pebbles. Numerical analyses pointed to some minor differences in their shape and size, but micropaleontological analyses revealed clasts of Carboniferous, Permian, Triassic, Jurassic, Cretaceous, Paleogene and Neogene age. Most of the Mesozoic and Cenozoic clasts originate from the two local mountain areas (Medvednica Mt. and Samobor Hills), with part of the Jurassic-Cretaceous pebbles possibly derived from SW Slovenia. Irregularly shaped and sometimes poorly rounded clasts of the Paleogene/Neogene ages seem to be abruptly transported to short distances by torrents or streams. The most enigmatic were the clasts of Carboniferous-Permian age. The nearest Palaeozoic outcrops occur upstream in Central Slovenia, but some fossils point to the even longer transport route, from the Karavanks in the upper flow of the Sava River. Gravels are overlain by fine-grained lake sediments and peat coal. Peat comprises significant amount of pine pollen, pointing to the warming period within the Late Pleistocene, which was additionally confirmed by the radiocarbon dating.